Industrialization and Urbanization in Turkey at the beginning of the 20th Century - Senem Zeybekoglu Sadri (Journal of Contemporary Urban Affairs, 2020)
The starting point of this study is the fact that every production system entails a specific spatial organization and changes its physical environment.  This research is an attempt to understand the industrialization period of Turkey’s Early Republican Period (1930’s) and the spatial effects of the new production system. Right after the Turkish War of Independence, The Republican Government of Turkey had aimed to establish an independent country and started to carry out a modernization and contemporization project. This project had different dimensions appealing to the institutional, economical, social and civic aspects of Turkey.  The economical dimension included the industrialization and economical independence of Turkey. Besides its economical, political and social goals, the Republican Government had aimed to change the physical appearance of the country. The Government’s first goal was to turn the country into the space of the National Turkish Republic State from an empire’s land. Secondly, the small towns or settlements of the country we're supposed to become modern cities, the places of modernity, just like the modern cities of the industrial and developed countries of the world.  That explains why the factories which were set up all around the country had played such a crucial role in the modernization period of Turkey at the beginning of the Republican era. They were not only economic achievements of the state; they also affected their physical and social environments and introduced the modern way of living particularly where they were set up.